Implementation of longitudinal welding stresses into structural calculation of steel structures - Pasternak, Hartmut; Kubieniec, Gabriel (Journal of Civil Engineering and Management, 2015)
During welding of typical steel cross sections, like T or I- Profiles e.g., residual stress occurs and need to be considered during the design process. With knowledge of the stress state after welding, farther calculation with different models are carried out. The systematic study will show three steps of the Okerblom's model to consider in the evaluation process of the welding stresses. The results of the numerical simulation and experimental models are show and compared. With that, the difference between the buckling curve from EN 1993-1-1 (2006) and the study are shown for steel S235 and S460. Especially for the high strength steels, the nowadays design conditions are very conservative and further investigation is needed and recommended.